Quartermaster supplies, equipment and services during operations in extreme cold. - Troutman, J. C. (Fort Leavenworth, KS : US Army Command and General Staff College, 1943)
This is a study of Quartermaster supplies, equipment and services for use in operations where the temperature may be as low as -20 degrees Fahrenheit. Consideration is given to operations both in mountains and sub-Arctic. Terrain, climate, clothing and messing, tentage/shelter, animal transport, pack boards/skis/snowshoes, and supply and maintenance are also included as topics.